A physical activity intervention for children with type 1 diabetes: Steps to Active Kids with Diabetes (STAK-D): a feasibility study - Quirk, Helen; Glazebrook, Cris; Blake, Holly (BioMed Central, 2018)
Background: This study describes the development and feasibility evaluation of a physical activity intervention for children with type 1 diabetes called ‘Steps to Active Kids with Diabetes’ (STAK-D). It aims to explore the feasibility and acceptability of the intervention and study design. Methods: Thirteen children aged 9-11 years and their parents were recruited from one paediatric diabetes clinic. A process evaluation was conducted alongside a two-arm randomised feasibility trial, including assessment of rate of recruitment, adherence, retention, data completion and burden, implementation fidelity and adverse events. Qualitative interviews with children (n=9), parents (n=8), healthcare professionals (n=3) and STAK-D volunteers (n=8) explored intervention acceptability. Interviews were analysed thematically. Results: Rate of recruitment was 25%, with 77% retention at 3-month follow-up. Study burden was low, data completion was high and the intervention was delivered as per protocol. No serious adverse event was reported. Engagement with intervention materials was generally good, but attendance at group activity sessions was low due to logistical barriers. Interview analysis identified preferred methods of recruitment, motivations for recruitment, barriers and facilitators to adherence, the experience of data collection, experience of the STAK-D programme and its perceived benefits. Conclusions: STAK-D was feasible and acceptable to children, their parents and healthcare professionals, but group sessions may present logistical issues. Recruitment and retention may be improved with a clinic-wide approach to recruitment.